Социальное партнерство высших учебных заведений: методологические подходы к оценке эффективности взаимодействия вузов с внешней средой - Манахов, С.В. (Культура народов Причерноморья, 2013)
В статье рассмотрены основные подходы к оценке эффективности взаимодействия
высших учебных заведений с ключевыми социальными партнерами, сделан вывод о необходимости
усовершенствования инструментария оценки, систематизированы наиболее общие оценочные
показатели результативности работы вузов в области социального партнерства, предложены два
подхода к оценке эффективности системы партнерства. По каждому из представленных подходов
приведены математические формулы расчета эффективности партнерства. У статті розглянуто основні підходи до оцінки ефективності взаємодії вищих навчальних
закладів з ключовими соціальними партнерами, зроблено висновок про необхідність удосконалення
інструментарію оцінки, систематизовано найбільш загальні оціночні показники результативності
роботи ВНЗ у галузі соціального партнерства, запропоновані два підходи до оцінки ефективності
системи партнерства. По кожному з представлених підходів наведені математичні формули
розрахунку ефективності партнерства. The article discusses the basic approaches to the estimation of efficiency of interaction between
higher educational establishments and the key social partner; the conclusion about the need to improve the
instruments for evaluation is made, the most common estimation criteria of the higher educational institutions
effectiveness in the field of social partnership are systematized, among which: demand for graduates in the labor
market; demand for the educational institution in the market of educational services; the presence in the reportplanning
and regulatory documentation of the educational establishment activities on social partnership; the
realization of educational establishments of different forms of cooperation with the social partners and others.
Two author's approaches to evaluating the effectiveness of the system of social partnership are offered and
justified: through the increase of its role in the organization and regulation of the labor market on the territory,
increase of a level of satisfaction of the demand for jobless and applications of enterprises for qualified specialists; through evaluation of the effectiveness of the labor potential. Mathematical formulas to calculate the
effectiveness of the partnership are given for each of these approaches.